The Impact Of Digital Technology On Learning Methods In Primary Schools - Nur Afidatun Nimah; Marno Nurullah; Samsul Susilawati (Journal Neosantara Hybrid Learning, 2024)
Nowadays, technology has brought a huge impact on education. This research discusses the impact of the application of digital technology on learning methods in elementary schools. Data was obtained from observations, interviews from several teachers who have applied digital technology in the learning process, secondary data from books, journals, and others. The results can be concluded that there are several positive and negative impacts of the application of digital technology in learning: 1) It makes it easier for teachers in the learning process, media and learning methods, 2) Students are easier to receive and understand material from the application of learning technology as a medium or learning method, 3) Learning becomes interactive and fun. Digital technology allows teachers to provide services without having to face students directly so that it can increase efficiency in the learning process. Negative impact: sometimes there are students who are dependent on digital technology which can lead to the loss of critical and creative thinking skills, social skills, and independent learning abilities due to searching habits and the like.